ANALISIS PENYALAHGUNAAN TROTOAR OLEH PEDAGANG KAKI LIMA DI KOTA BOGOR DALAM HUKUM TATA RUANG - Yusran Al Miski; Muhamad Rizki Ramadhan; Fajar Juniar; gisca amalia putri; Satria manggala putra; Nur Lailla Permasari; Shalima Nayla Rizkia; Syauqi al gifari Akmal; Ilyas Josadi Josadi; Muhammad Iqbal Purwanto (Jurnal Perspektif Hukum, 2025)
Sidewalk abuse in Bogor City has become a serious problem and interferes with the comfort and safety of pedestrians. This study examines the legal aspects regarding the use of sidewalks that deviate from their function, such as by street vendors, parked motor vehicles, and other activities that cause obstacles for pedestrians. With a normative approach and juridical study, this study examines related laws and regulations, law enforcement, and challenges in their implementation in the field. The results of the study show that there is still weak supervision and legal sanctions applied, so that the abuse of sidewalks continues. This study recommends increasing regulations, strict law enforcement, and public education to restore the function of sidewalks as safe and comfortable facilities for pedestrians in Bogor City.